Internal and external cohesion in the english simultaneous interpreting of arabic political discourse: with reference to hassan nasrallah's sixty-frist nakba speech - Kamal,Mona Alaa El-din Mohammed; Cairo University, Faculty of Arts ([N.P]: [N.P], 2014)
Arabic summary .
vol. II
(MS) - Cairo University : Faculty of Arts,2014.
Keywords: Arabic Political .